Iqbal’s ego philosophy and its importance in awakening man’s spirituality - Abdul Razak, Mohd Abbas (International Islamic University Malaysia, 2014)
History reveals the fact that the coming of modernity and secularism has allured modern man towards a materialistic concept of life, ignoring his spiritual needs in respect of his role as the vicegerent of God. This predicament has not only marred man’s relationship with God but has also failed him toward understanding his true nature and mission in life. The large segment of humanity today is on the brink of losing its human and spiritual values, resulting in severe environmental degradation, racism, terrorism, war, poor mental health, and other psychopathological illnesses. This paper intends to explore and draw out conclusions from the philosophical thoughts of Muhammad Iqbal (1877-1938) with regard to his ego philosophy that explains man’s relationship with God, community and the universe (flora and fauna). Lessons drawn out from Iqbal’s ideas can be of great use in awakening man’s spirituality and improving his quality of life by establishing a harmonious relationship with God, environment and fellow human beings.